I paint what I see - Wilson, Gahan (Simon and Schuster, 1971)
Here, for treasuring, traumatizing, and delighting is the fiendish universe of Gahan Wilson. A featured Playboy and National Lampoon cartoonist, Wilson draws our unspeakables and gives shapes to our unthinkables with a demoniacal accuracy that delights and shocks. I paint what I see is a wild experience in over 100 marvelously depraved cartoons guaranteed to transport the reader in a very special world.